INSPIRING INNOVATIVE LIBRARY SERVICES FOR COVID-19 INFORMATION DISSEMINATION (NAU Journal of Library and Information Science, 2022)
Present day library services are IT driven. Rapid technological advances in information and communication technology have enabled the provision of library and information services beyond the four walls of the library building. With this development, it is possible to render library services online via library portals and websites. This has enhanced library services around the world. The outbreak of COVID 19 disease has affected the nature and structure of library services. The contagious nature of the outbreak of the disease forced many public institutions to shut down at the hit of the disease in 2020. Libraries as public institutions were shut down but the information needs of their users remained unsatisfied. Added to this is the increasing growth in the number of information service providers who feed the information seeker with both filtered and unfiltered information resources. For libraries to meet the information needs of its users and to continue to remain relevant, libraries need to restrategise and create innovative services in line with the WHO safety protocol. In this regard, libraries now consider using massively Online Public Access Catalogs (OPAC) and networked databases, personal space / my library, Short Message Service (SMS) notification, Quick Response (QR) codes, online / text reference services, library portals among others as innovative approaches to library users' information dissemination. These form the focus of this paper.
Keywords: Libraries; COVID 19; WHO; Innovative Services; OPAC; Quick Response Services